The nitrergic mechanism of geraniol in PTZ-induced seizures - Babak Shahhosseini; Hossein Tahmasebi Dehkordi; Hossein Amini-Khoei; Antoni Sureda; Mehrdad Shahrani; Zahra Lorigooini (IBRO Neuroscience Reports)
Background: This investigation aims to elucidate the role of NO in the anticonvulsant effects of Geraniol (GER) using a mouse model of pentylenetetrazole (PTZ)-induced seizures. Methods: Mice were allocated into ten groups, including a control group receiving normal saline. The treatment groups received GER (10, 20, 30, and 40 mg/kg), L-NAME (10 mg/kg), L-arginine (L-arg) at 150 mg/kg, a sub-effective dose of GER (10 mg/kg) combined with L-NAME, and an effective dose of GER (40 mg/kg) plus L-arg, respectively. All drugs were administered intraperitoneally 30 min before seizure induction by intravenous infusion of PTZ. The last group served as the control for biochemical and molecular tests (no seizure induction). Subsequently, the seizure threshold was recorded. Nitrite levels in serum and the prefrontal cortex (PFC), as well as the gene expression of nNOS and iNOS in the PFC, were assessed. Results: GER prolonged the seizure threshold and reduced serum and PFC nitrite levels. Also, it downregulated the gene expression of nNOS and iNOS. Simultaneous administration of L-arg with the effective GER dose (40 mg/kg) notably reversed the beneficial effects of GER. Conversely, when administered with a sub-effective dose of GER (10 mg/kg), L-NAME potentiated the effects of this dose of GER. The expression of the nNOS gene in the PFC significantly increased following the administration of 20 mg/kg GER and L-arg plus 40 mg/kg GER. Conversely, 40 mg/kg GER alone reduced nNOS gene expression in the PFC. Conclusion: GER exhibits anticonvulsant properties by modulating the nitrergic system, increasing seizure latency, and reducing NO production. This suggests its potential as a therapeutic candidate for seizure management.